Strategi Pengembangan UMKM Melalui Literasi Keuangan Digital di Desa Nukuhai - Cynthia Petra Haumahu; Krisman Gea; Helnida Wati Telaumbanua; Dina Resley; Diva Tiara Lumban Batu; Recky Gregory Frans (MAN 4 Kota Pekanbaru, 2026)
This study analyzes the development strategy of micro, small, and medium enterprises (MSMEs) in Nukuhai Village through the strengthening of digital financial literacy. The research uses a descriptive qualitative approach supported by field observation, semi-structured interviews with MSME actors and village stakeholders, participatory problem mapping, and document review. The findings show that MSME development in Nukuhai is constrained by limited financial recordkeeping, weak separation between household and business finance, low familiarity with digital payment instruments, limited product standardization, and uneven access to digital marketing infrastructure. Digitalization therefore cannot be treated merely as the use of social media or online platforms; it must be preceded by basic financial literacy, simple bookkeeping, secure transaction behavior, product improvement, and collective marketing support. The study proposes a gradual village-based strategy that integrates financial recording, QRIS adoption, digital promotion, packaging improvement, cooperative logistics, and actor-based implementation support. These findings contribute to rural MSME studies by emphasizing the importance of context-sensitive digital capacity building in archipelagic villages.